In situ X-ray diffraction study of decomposition kinetics in LaSrCoO4 at a low partial pressure of oxygen - Pomiro, Federico José; Bohe, Ana Ester; de Micco, Georgina (Elsevier Science SA, 2019)
Fil: Pomiro, Federico José. Comisión Nacional de Energía Atómica. Gerencia Complejo Tecnológico Pilcaniyeu; Argentina